Nanoemulsion-Based Delivery Systems to Improve Functionality of Lipophilic Components - Odriozola-Serrano, Isabel; Oms-Oliu, Gemma; Martín-Belloso, Olga (Frontiers in Nutrition, 2014)
The use of active lipophilic substances such as antimicrobials and health-related compounds in the food industry still is a challenge due to their poor water-solubility and instability in food formulations. Nano-sized structures such as nanoemulsions of oil-in-water are regarded as useful tools with a great potential in the food sector to incorporate food ingredients. Reducing the size of the active compounds incorporated within a solution would increase the surface area per mass unit of nanoemulsions thus enhancing solubility and stability in foods. In addition, the ability of the active lipids to penetrate across biological membranes is also enhanced, thus boosting their biological functionality. An overview of the most significant studies reporting data about the potential benefits of active lipid nanoemulsions over conventional emulsions is presented.